2019
DOI: 10.1111/jne.12810
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of prepubertal dynorphin secretion in the medial basal hypothalamus of the female rat

Abstract: The onset of puberty is the result of an increase in secretion of hypothalamic gonadotrophin‐releasing hormone (GnRH). This action is a result of not only the development of stimulatory inputs to its release, but also the gradual decrease in inhibitory inputs that restrain release of the peptide prior to pubertal onset. Dynorphin (DYN) is one of the inhibitory inputs produced in the medial basal hypothalamus (MBH); however, little is known about what substance(s) control its prepubertal synthesis and release. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 71 publications
3
14
0
Order By: Relevance
“…While the above in vitro study suggested that NKB inhibits DYN secretion, animal studies were needed to discern a better understanding of this action within the MBH. In this regard, that same study [87] showed an increase in protein expression of the NK3R (Fig. 3a), along with suppressed protein expressions of DYN (Fig.…”
Section: Action Of Nkb On Prepubertal Dyn Secretionmentioning
confidence: 55%
See 2 more Smart Citations
“…While the above in vitro study suggested that NKB inhibits DYN secretion, animal studies were needed to discern a better understanding of this action within the MBH. In this regard, that same study [87] showed an increase in protein expression of the NK3R (Fig. 3a), along with suppressed protein expressions of DYN (Fig.…”
Section: Action Of Nkb On Prepubertal Dyn Secretionmentioning
confidence: 55%
“…Therefore, it was important to determine whether the tachykinin, NKB, which increases in the MBH as puberty approaches [86], would cause the suppression of prepubertal DYN release and thus facilitate the pubertyrelated rise in GnRH/LH secretion [20,82]. An initial study [87] assessed MBH explants from late juvenile female rats exposed to senktide, an NK3R agonist, and revealed a dose-dependent inhibition of DYN release, which coincided with an increase in GnRH release from the same tissue block. That same study also showed that both actions of senktide were blocked by the prior central administration of an antagonist to NK3R.…”
Section: Action Of Nkb On Prepubertal Dyn Secretionmentioning
confidence: 99%
See 1 more Smart Citation
“…While prenatal ethanol exposure did not result in sex differences [56,57], it is possible that ethanol exposure during the peri-pubertal period may affect the dynorphin/KOR system in adulthood. Secretion of dynorphin in the hypothalamus reduces at the onset of puberty in female rats [61]. Alcohol exposure between PD 27 and 33 in female rats, however, resulted in elevated synthesis of dynorphin in this region [62].…”
Section: Discussionmentioning
confidence: 94%
“…While prenatal ethanol exposure did not result in sex differences [ 60 , 61 ], it is possible that ethanol exposure during the peri-pubertal period may affect the dynorphin/KOR system in adulthood. Secretion of dynorphin in the hypothalamus decreases at the onset of puberty in female rats [ 65 ]. Alcohol exposure between PD 27 and 33 in female rats, however, results in elevated synthesis of dynorphin in this region [ 66 ].…”
Section: Discussionmentioning
confidence: 99%